BUDAYA PESISIR: Perilaku Konsumtif Masyarakat Tambaklorok, Kelurahan Tanjung Mas, Kecamatan Semarang Utara, Kota Semarang - Rini Susiana (Fakultas Ilmu Budaya Universitas Diponegoro, 2018)
The coastal community in the Tambaklorok area does not only work as fishermen as their livelihood. This study aims to determine (1) the social stratification of Tambaklorok community, (2) the similarities and differences in consumer behavior of Tambaklorok community, and (3) the characteristics of consumer behavior of Tambaklorok community. The study uses a qualitative approach. Data collection was carried out through in-depth interviews, observation and analyzing documents. Analysis of data uses an interactive model of Miles and Huberman, including data collection, data reduction, drawing conclusion, verification, and data presentation. The result shows that social stratification of Tambaklorok community based on livelihood, namely the fishermen, fish distributors, fish processors, and civil servants. There are various similarities and differences in consumer behavior of Tambaklorok community seen from the income, expenses and debts. Characteristics of consumer behavior of Tambaklorok community that is impulsive purchasing, includes buying the product in order to maintain personal appearance and prestige as well as of chasing the prize.